Study of miniature features generated by backside patterned texturing in precision diamond machining - Ahmed Syed Adnan (2018)
Structured and functional surfaces are key components in many advanced technological applications, such as electronics, information technology, energy, optics and tribology. A gamut of products has emerged where the surfaces are specially textured or engineered for a particular function. These textured surfaces rely on the control of surface characteristics to obtain the desired functional performance. Various techniques and methods have been used to develop micro-scale functional surfaces. For example, ultraprecision single point diamond turning (SPDT) and its associated processes, such as fast tool servo (FTS) and slow slide servo (SSS) have been used to fabricate various types of micro-sized surface textures. However, these techniques have limitation to produce surface features at submicron scale. In addition, the existing associated methods of SPDT require a complex tool path programming for the tool-workpiece synchronized motion for asymmetric and freeform surface generation. This thesis attempts to address the limitations of SPDT and its associated specialized techniques and to propose a potential alternative: backside patterned texturing (BPT) for submicron to micro-sized surface features generation on the diamond machined surface.